Factor influencing electronic nursing documentation in type C Private Hospitals Pekanbaru - Fitra Mayenti; Dwi Yunita Rahmadhani; Ahmad Redho; Tengku Isni Yuli Lestari Putri (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2026)
Background: Electronic Nursing Documentation (EDN) practices in Class C hospitals are crucial for implementing the current care system. However, EDN practices in developing cities like Pekan Baru have not been fully implemented, and the factors influencing them remain poorly understood. Objectives: This study aims to analyze the factors influencing electronic nursing documentation among nurses in inpatient wards at Class C hospitals in Pekan Baru City. Methods: This is an observational, analytical, cross-sectional study. The study was conducted at three private Class C hospitals in Pekanbaru: Ibnu Sina Hospital, Syafira Hospital, and Sansani Hospital. Data were collected through questionnaires from 173 nurses who met the inclusion and exclusion criteria. Factors such as demographics, psychological conditions, job satisfaction, stress, personality, organizational factors, and work compensation systems were measured. Analysis used chi-square analysis followed by multiple logistic regression. Results: In this study, hospital type, age, education, biological stress, supervisory organizational factors, and rewards system were significantly associated (p-value < 0.05), while other factors were not. Multivariate analysis revealed that five variables significantly associated nurse documentation: age, education level, biological stress, supervision, and reward systems (p < 0.05). Supervisory organizational factors (OR = 15.429) and reward systems (OR = 8.657) were the most dominant. Conclusions: The finding indicate that supervision and institutional incentive system are significantly associated with electronic nursing documentation practice among nurse. Nurse with better supervision and more supportive reward systems tended to demonstrate improve documentation practices. These findings suggest that organizational factor may contribute to supporting electronic documentation, although further longitudinal or experimental studies are needed to confirm causality.